Substance dependence among those without symptoms of substance abuse in the World Mental Health Survey. Issue 3 (17th February 2017) - Lago, Luise; Glantz, Meyer D.; Kessler, Ronald C.; Sampson, Nancy A.; Al‐Hamzawi, Ali; Florescu, Silvia; Moskalewicz, Jacek; Murphy, Sam; Navarro‐Mateu, Fernando; Torres de Galvis, Yolanda; Viana, Maria Carmen; Xavier, Miguel; et al.
Abstract: The World Health Organization (WHO) World Mental Health (WMH) Survey Initiative uses the Composite International Diagnostic Interview (CIDI). The first 13 surveys only assessed substance dependence among respondents with a history of substance abuse; later surveys also assessed substance dependence without symptoms of abuse. We compared results across the two sets of surveys to assess implications of the revised logic and develop an imputation model for missing values of lifetime dependence in the earlier surveys. Lifetime dependence without symptoms of abuse was low in the second set of surveys (0.3% alcohol, 0.2% drugs). Regression‐based imputation models were built in random half‐samples of the new surveys and validated in the other half. There were minimal differences for imputed and actual reported cases in the validation dataset for age, gender and quantity; more mental disorders and days out of role were found in the imputed cases. Concordance between imputed and observed dependence cases in the full sample was high for alcohol [sensitivity 88.0%, specificity 99.8%, total classification accuracy (TCA) 99.5%, area under the curve (AUC) 0.94] and drug dependence (sensitivity 100.0%, specificity 99.8%, TCA 99.8%, AUC 1.00). This provides cross‐national evidence of the small degree to which lifetime dependence occurs without symptoms of abuse. Imputation of substance dependence in the earlier WMH surveys improved estimates of dependence.